Seni Beatbox pada Nasyid Islami dalam Perspektif Hukum Islam - Maqsurah, Ainil; Bakry, Kasman; Jannah, Sa’adal (BUSTANUL FUQAHA: Jurnal Bidang Hukum Islam, 2020)
Legal discussion about music in Islam is a forbidden matter. Although there are opinions that allow, but this opinion is weak with the arguments of the Qur'an, the traditions and ijmak of the scholars of the Salaf in their forbidden. The beatbox in Islamic nasheed is in the form of rhythmic sounds such as drum beats, musical instruments, or imitations of other sounds, especially turntables, through human speech instruments such as the mouth, tongue and lips that accompany Islamic nashid as the sounds musical instrument replacement. The purpose of this study was to determine the beatbox law in Islamic nasyid. The research method applies qualitative studies with library research methods and descriptive analysis and uses a normative approach. The results showed that the legal consequences of beatbox art were indeed discussed by the scholars, but the strongest opinion was that it was not allowed. The sounds that come from the human body and the sound resembles the sound of a musical instrument, so the law is haram, both playing it and hearing it. As for Islamic nasheed which does not contain forbidden cases, then the law may.